ChemInform Abstract: One‐Pot Synthesis of N‐(α‐Peroxy)Indole/Carbazole via Chemoselective Three‐Component Condensation Reaction in Open Atmosphere. Issue 14 (March 2016) - Wang, Xinbo; Pan, Yupeng; Huang, Kuo‐Wei; Lai, Zhiping
Abstract: The title compounds are prepared as potential building blocks for the synthesis of mycotoxins Fumitremorgin A and Verruculogen or their derivatives.